A combination of alfaxalone, medetomidine and midazolam for the chemical immobilization of Rhesus macaque (Macaca mulatta): Preliminary results. Issue 6 (21st September 2017) - Bertrand, Henri G. M. J.; Sandersen, Charlotte; Murray, Jennifer; Flecknell, Paul A.
Abstract: Background: Chemical immobilization of non‐human primates can be required to perform scientific or veterinary procedure with different invasiveness degrees. This preliminary study was undertaken to assess the clinical effects of a combination of alfaxalone, medetomidine and midazolam (AMM). Methods: Seven rhesus macaques were chemically immobilized, for invasive veterinary procedures, with alfaxan 2 mg kg −1, medetomidine 20 μg kg −1 and midazolam 0.3 mg kg −1 injected subcutaneously. Results: The alfaxalone combination induced surgical anaesthesia, with a complete absence of response to noxious stimuli, for at least 20 minutes. The total duration of anaesthesia was 56 ± 7 minutes, and the administration of atipamezole, to partially reverse the combination effects, did not appear to alter the depth of anaesthesia. Conclusion: In conclusion, the AMM combination produced rapid onset general anaesthesia, following subcutaneous administration of a relatively low volume (0.28 mL/kg) of injectate.